Dressing Management during Total Knee Arthroplasty: A Systematic Review and Meta-Analysis - Chen, Zhongming; Bains, Sandeep S.; Sax, Oliver C.; Sodhi, Nipun; Mont, Michael A. (The Journal of Knee Surgery, 2022)
Dressings for total knee arthroplasty (TKA) typically focus on promoting optimal healing, while preventing infection, allowing for functionality and immediate ambulation, while providing for excellent cosmesis. We have previously described four aspects of closure after TKA involving the: (1) deep fascial layer; (2) subdermal layer; (3) intradermal layer, including the subcuticular region; and (4) a specific aseptic dressing. In this meta-analysis and systematic review of the literature, we will focus on the dressing. Specifically, we assessed: (1) infection risk of different techniques; (2) re-operation or readmission risk; and (3) length of time until dressing change needed. There were 16 reports on infection risk, re-operation risk, and length of time until change needed. A meta-analysis focused on the qualifying wound complication risk reports was also performed. The meta-analysis including four studies (732 patients) demonstrated overall lower wound complication risk with the use of adhesives and mesh dressings (odds ratio 0.67) versus traditional closures. Additionally, studies demonstrated fewer re-operations and readmissions with the use of adhesives and mesh dressings. Furthermore, one report demonstrated mesh dressings persist longer than silver dressings. Therefore, multiple recent reports suggest superior outcomes when using adhesive and mesh dressings for TKAs.
Keywords: total knee arthroplasty; arthroplasty; wound management; suture; wound dressing